Math Questions and Answers

Start Your Free Trial

Describe and correct the error `` 2b^2+b=6 b^2+(1/2)b=3 b^2+(1/2)b+(1/2)^2=3+(1/2)^2 (b+(1/2))^2=3+(1/4) b+(1/2)=`+-` `sqrt(13/4)` b=(-1/2) `+-` (`sqrt(13)` /2) b= (-1`+-` `sqrt(13)` /2)

Expert Answers info

degeneratecircle eNotes educator | Certified Educator

calendarEducator since 2012

write290 answers

starTop subject is Math

There is an error in the process of completing the square on the left hand side while going from line 3 to line 4, since

`b^2+1/2b+(1/2)^2!=(b+1/2)^2.` 

A correct solution starting at line 3 would be

`b^2+1/2b+(1/4)^2=3+(1/4)^2`

`(b+1/4)^2=3+1/16`

`b+1/4=+-sqrt(49/16)`

`b=-1/4+-7/4`.

This gives the two solutions `b=3/2` and `b=-2.`

check Approved by eNotes Editorial